Dependence of the geothermal gradient on the position of hydrocarbon deposits in the Dnieper-Donets basin - Usenko, A.P. (Reports of the National Academy of Sciences of Ukraine, 2014)
During the calculation of the heat flow at 39 fields of the northwestern part of the Dnieper-Donets basin, the principles of geothermal gradient distribution are determined and analyzed. The gradient dependence on the tectonic structure (location of hydrocarbon deposits and placement of faults) and the display of a hydrogeological inversion are studied. The presence and the location of hydrocarbon deposits are likely related to the inflow of a deep hydrothermal solution via permeable fault zones.